Direct Robotic Extrusion of Photopolymers (DREPP): Influence of microgravity on an in-space manufacturing method - Kringer, Michael; Böhrer, Christoph; Frey, Moritz; Pimpi, Jannik; Pietras, Markus (Frontiers in Space Technologies, 2022)
A method using Direct Robotic Extrusion of Photopolymers (DREPP) to manufacture structures in space in a cost- and power-efficient way is presented in this article. In this novel manufacturing process, a photoreactive resin is robotically extruded through a nozzle and directly cured by UV-light. Unlike most conventional Additive Manufacturing (AM) methods, which manufacture layer-by-layer, the DREPP technology is able to create three-dimensional structural elements in one continuous movement. To investigate the feasibility under microgravity conditions, multiple experiments were performed on parabolic flights, where it was shown that different geometries can be successfully manufactured under microgravity conditions. When examining the printing process at zero gravity and 1 g, differences in the printing behaviour can be observed, which are investigated in detail. In addition to this, the evaluation shows that a large curing zone - the transition area between the liquid and cured state of the extruded resin – is easier to handle in zero gravity than under 1 g conditions. This contributes to an increased overall process stability and could have the potential to enable new ways for controlling the process. This technology is expected to outperform conventional deployable structures, which generally suffer from severe limitations: long and high-cost development phases, oversized elements to survive the high launch loads, mechanical complexity as well as constraints to the maximum structure size due to the limited volume in a satellite. In-Space Manufacturing (ISM) and especially AM offer a solution to circumvent these limitations. Fundamental investigations on AM in space have already been carried out on the International Space Station (ISS). Numerous test prints have shown that Fused Filament Fabrication (FFF) provide satisfactory results under microgravity and controlled environmental conditions. This article will conclude with an outlook on future investigations of the DREPP approach and preparations for experiments in microgravity and vacuum on a sounding rocket.